Towards IR4.0 implementation in e-manufacturing: artificial intelligence application in steel plate fault detection - Adeleke Abdullahi; Noor Azah Samsudin; Mohd Rasidi Ibrahim; Muhammad Syariff Aripin; Shamsul Kamal Ahmad Khalid; Zulaiha Ali Othman (Institute of Advanced Engineering and Science, 2020)
Fault detection is the task of discovering patterns of a certain fault in industrial manufacturing. Early detection of fault is an essential task in industrial manufacturing. Traditionally, faults are detected by human experts. However, this method suffers from cost and time. In this era of Industrial revolution IR 4.0, machine learning (ML) methods and techniques are developed to solve fault detection problem. In this study, three standard ML models: LR, NB, and SVM are developed for the classification problem. The experimental dataset used in this study consists of steel plates faults. The dataset is retrieved from UCI machine learning repository. Three standard evaluation methods: accuracy, precision, and recall are validated on the classification models. Logistic regression (LR) model achieved the highest accuracy and precision scores of 94.5% and 0.756 respectively. In addition, the SVM model had the highest recall score of 0.317. The results showed the significant impact of AI/ML approach in steel plates fault diagnosis problem.